The effectiveness of the problem-based learning model with mind map supplements improves the critical thinking ability of grade IV students of SD Inpres Roja 2, Ende City - Sunimbar Suni; Ummu Aiman; Farhan Syuhada (Elementary Education Study Program School of Postgraduate Studies Universitas Pendidikan Indonesia in collaboration with UPI PRESS, 2023)
The purpose of this study is to determine the effectiveness of problem-based learning learning models with mind map supplements to improve the critical thinking skills of grade IV students of SD Inpres Roja 2 Kota Ende. The type of research used is pre-experimental design with one group pre-test -post test design design. The population of this study was all grade IV students of SD Inpres Roja 2 Kota which amounted to 24 people. The sampling technique used is non probability sampling with a saturated sampling type. Data collection techniques in this study are in the form of multiple choice tests and essays. Data on the implementation of the problem-based learning model with the supplement of mind maps improved critical thinking skills at meeting I with a score of 75% in the good category and the second meeting with a score of 85.4% in the excellent category. Data on the critical thinking ability of students were tested for normality by the kolmogorov smirnov method and then tested for homogeneity in the variance test. The results of this test show that the distributed data is normal and homogeneous. Hypothesis testing using the t-test obtained a t-count of 11.445 while the t-table at a significant level of 5% was 2,019. The results show that the t-count is greater than the t-table so that it can be inferred Ha in the received and H0 in the rejected. The effectiveness of the Problem Based Learning Model learning model with mind map supplements Improving critical thinking skills Grade IV students of SD Inpres Roja 2 Kota Ende were tested for effect size using the cohen's effect size formula, the results showed 2.62 with a range of criteria in the cohen's formula, which is 0.8-2.0 which is classified as high based on the classification of the effect size test, which means that the problem-based learning learning model with the supplement of the mind map is effective in improve critical thinking skills.